Blood pool contrast agents for venous magnetic resonance imaging - Oliveira, Irai S.; Hedgire, Sandeep S.; Li, Weier; Ganguli, Suvranu; Prabhakar, Anand M. (Cardiovascular Diagnosis and Therapy; Vol 6, No 6 (December 29, 2016): Cardiovascular Diagnosis and Therapy (Advanced Venous Imaging and Image-guided Venous Interventions), 2016)
Imaging of the venous system plays a vital role in the diagnosis and management of a wide range of clinically significant disorders. There have been great advances in venous imaging techniques, culminating in the use of magnetic resonance venography (MRV). Although MRV has distinct advantages in anatomic and quantitative cross sectional imaging without ionizing radiation, there are well-known challenges in acquisition timing and contrast administration in patients with renal impairment. The latest advancement involves the addition of new contrast media agents, which have emerged as valuable alternatives in these difficult scenarios. In this review, we will focus on a group of specific contrast agents called blood pool agents and discuss their salient features and clinical applications.